Intercropping of Medicinal Plants with Poplar and their Phenology - Jha, Kaushalendra Kumar; Gupta, Chandra (Indian Forester, 1991)
In taral region Intercropplng of some medicinal plants with Poplar as principal crop as carried out during 1987-89. Out of sixty-four species tried Acorus calamus. Adhatoda rasiea, Aloe barbadense, Artimicia vulgaris, Canabis sativa, Centella asiatica, Curcuma amada. C. longa, Cymhopogon winterianus, Cyperus. Scariosus, mimosa pudica, Piper longum, Solamum indicum, Veliveria zizanoides, Amomum subulatum, Calotropis giganlia, Cymbopogon jwarencusa, Ocimum sanctum, Plantago avataforsk, Valaerina wallichii and Zingiber officinale were found most suitable. The species which showed poor performance are Abrus precatorious, Cinnamomum zeylanicum. Cymbopogon martini, Mentha citrata, Premna latifolia, Salvadora oleoides, Tribules lerrestris. Wilhania somnilera and Woodfordia fruticosa. The growth of different clones of Poplar was found to be improved due to intercropplng operations. During the intercropping trial phenology of different medicinal species wso also studied.